Storehouse and sanctuary: the role of Brazil in world food security - Pires Tiburcio, James Augusto; Bursztyn, Marcel (Fronteira: Journal of Social, Technological and Environmental Science, 2013)
Natural endowments such as land availability, abundant water, fertile soils, and favorable climate combined with decreasing population growth place Brazil as the leading force in world food production. Brazil is also the guardian of the most diverse eco-systems in the planet and is continuously wrestling between the expansion of the agricultural land area and the preservation of the most diverse fauna and flora, embodied in the Amazon forest. Addressing the international political economy of trade and food security from a Brazilian perspective, this paper argues that the main obstacles facing Brazil in food security are not domestic, but international. International political issues are at the core of the most relevant hurdles and understanding the reciprocal relationship between world food security and the emerging economies position especially that of Brazil in food production and trade is crucial. I argue that comprehending the elements that constrain the present and future role of Brazil in fulfilling its potential as food supplier in an ecologically and economically sustainable path, as well as its new found role as agricultural cooperation partner in the promotion of a food safe world is paramount if the world is to feed 7 billion mouths.